Analisa Manajemen Resiko Keamanan Sistem Informasi Baznas Kampar dengan Metode Failure Mode And Effect Analysis (FMEA) - Alriwanda, A; Saputra, Eki; Megawati, M; Ahsyar, Tengku Khairil (LPPM STIKOM Tunas Bangsa, 2024)
Risk management is a key element in an organization's activity strategy, one of the existing risk management methods is Failure mode effect and analysis (FMEA). Many researchers use this method to determine the risks that exist in the company. This research was conducted at the National Zakat Amil Agency (BAZNAS) Kampar using FMEA to determine the risks that exist at BAZNAS. In the research, the Risk Priority Number (RPN) was calculated by multiplying Severity, Occurance and Detection. The results obtained in research using FMEA produced 5 failure modes, namely Data, Hardware, Software, People / Human Error and Network and provided recommendations to BAZNAS